Performance of honey bess (Apis mellifera L.) in three ecosystems in Laguna, Philippines - Fajardo, Analinda C. Manila; Cervancia, Cleofas R. (2003)
The population growth rates, pollen spectra and honey produced in managed and unmanaged colonies of honeybees (Apis mellifera) were compared in three ecosysterns in Laguna Experiments were conducted at the Canlubang Industrial Estate, in the town of Bay and in the Makiling Forest Reserye representing the industrial, agricultural and forest environments, respectively, from August 30, 2000 to May 2002.

The population growth of A. mellifera in an agroecosystem was significantly higher than in the industrial and forest environments. The abundance of melliferous plants in the agroecosystem enhanced the population build-up of A. mellifera. The native species, Apis cerana and Apis dorsata, negatively affected the growth of A. mellifera colonies in the forest ecosystem by aggression and robing of stores. Mites, Varroa destructor, chalk brood disease and bird predators were observed in all sites.

Among the three environments studied, the bees performed best in the agroecosystem in terms of population growth and honey production. Trace amounts of cadmium, lead and chromium were detected in pollen samples from the industrial ecosystem. Deltametrin and cypermetrin were absent in the honey and pollen samples from the agroecosystem.

Fifty-one pollen types were identified from the samples. There was no predominant pollen source. Seven secondary pollen sources were identified: Hygrophila lancea, Acanthaceae type Convolvulaceae types, Mimosa diplotricha var. diplotricha, Mimosa pudica, Leguminosae types and Palmae types. Family Leguminosae represented most of the pollen types observed. There was an overlap in the pollen types identified from agroecosystem. the industrial ecosystem and the agroecosystem.

In spite of diversity in a forest ecosystem, the exotic species A. mellifera failed to exploit the nectar and pollen sources of most plant species. This indicates that A. mellifera has not indeed adapted to natural forest conditions in the tropics.
Keywords: Bees